Pengembangan Instrumen Penilaian E-Quiz (Electronic Quiz) Matematika Berbasis HOTS (Higher of Order Thinking Skills) untuk Kelas V Sekolah Dasar - Dian Fitri Nur Aini; Nawang Sulistyani (Universitas Muhammadiyah Enrekang, 2019)
The purpose of this study is to (1) produce a mathematical e-quiz assessment instrument based on HOTS (high order thinking skills) for grade V elementary school, (2) describe the feasibility of a mathematical e-quiz assessment instrument based on HOTS (high order thinking skills) for grade V SD. This research design uses the Lee and Owens development research model which consists of five stages, namely; (1) Assessment / Analysis which consists of two main parts namely Requirement Analysis and Front-end Analysis; (2) Design ; (3) Development ; (4) Implementation ; and (5) Evaluation. Data collection techniques using observation, documentation and questionnaires. Analysis of the data in this study is descriptive qualitative and quantitative analysis. The results showed that the product of the development met the validity aspect with a validation coefficient of 86,5%. The field trial results obtained a percentage of product practicality of 90%. HOTS (high order thinking skills) based e-quiz assessment instruments developed in this study were appropriate for use in learning assessments especially in mathematics because they met the criteria of validity and practicality.